Phylogeographic Studies Depict the Role of Space and Time Scales of Plant Speciation in a Highly Diverse Neotropical Region - Leal, Bárbara Simões Santos [UNESP]; Palma da Silva, Clarisse [UNESP]; Pinheiro, Fábio (Taylor & Francis, 2016)
Phylogeographic studies have merged different disciplines to explain speciation processes at both spatial and time scales. Although the number of phylogeographic extant studies has increased almost exponentially, few have been conducted in tropical countries, especially using plants. Plants are interesting models for such studies because their responses to different habitat conditions are reflected directly in the size and distribution of populations, enabling direct tests of alternative demographic scenarios. Here, we review phylogeographic studies using plant species occurring in different vegetation domains within Brazil, which has the greatest number of plant species in the world. Based on a detailed examination of 41 published articles, we synthesized the current knowledge and discussed the main processes driving the high levels of plant diversity within Brazilian domains. General patterns of diversification could be inferred due to the number of species studied, especially in the Cerrado and Atlantic Forest, the most intensively studied domains (34.1% and 17.1% of the studies, respectively). Distinct vegetation types within both biomes were affected differently by the Pleistocene climatic oscillations. Edaphic conditions and geographical barriers (rivers and mountains) have also influenced the phylogeographical patterns of plants species from Amazonia and the Atlantic Forest. Other Brazilian domains, such as the Caatinga, Pantanal, and Pampas, have been studied to a lesser extent and no common phylogeographic pattern across species could be inferred. Issues regarding past connections between distinct domains also remain unclear, including those affecting the two main forest domains in South America. Future research on plant species will fill these information gaps, improving our understanding of the complex diversification processes affecting the South American biota.
Keywords: biodiversity; microevolution; neotropics; phylogeography; population structure; species diversification